On the impact of carbohydrate-binding modules (CBMs) in lytic polysaccharide monooxygenases (LPMOs). Issue 3 (18th April 2023) - Forsberg, Zarah; Courtade, Gaston
Abstract: Lytic polysaccharide monooxygenases (LPMOs) have revolutionized our understanding of how enzymes degrade insoluble polysaccharides. Compared with the substantial knowledge developed on the structure and mode of action of the catalytic LPMO domains, the (multi)modularity of LPMOs has received less attention. The presence of other domains, in particular carbohydrate-binding modules (CBMs), tethered to LPMOs has profound implications for the catalytic performance of the full-length enzymes. In the last few years, studies on LPMO modularity have led to advancements in elucidating how CBMs, other domains, and linker regions influence LPMO structure and function. This mini review summarizes recent literature, with particular focus on comparative truncation studies, to provide an overview of the diversity in LPMO modularity and the functional implications of this diversity.